Vulvar Cancer with Cutaneous and Breast Metastases. (19th January 2021) - Adhikari, Nawaraj; Vennepureddy, Adarsh; Parylo, Sara; Agarwal, Anupma; Dhar, Meekoo
Abstract : Vulvar cancer accounts for about 5% of cancer of female genitalia. It may initially present as benign symptoms resulting in potential delay in diagnosis. Few cases of distant metastases to skin or breast have been reported. We present the case of a 76-year-old female with possible delay in diagnosis of her squamous cell carcinoma of vulva. After 4 months of the diagnosis, she presented with concurrent cutaneous and breast metastases.